UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA DENGAN TIPE TEAMS GAMES TOURNAMENT (TGT) SISWA KELAS XI IPA MAS TI BATANG KABUNG PADANG - Artati, Yuni - (Pendidikan Matematika, 2014)
The evaluation study of mathematic for student in class XI IPA MAS TI Batang Kabung Padang still low and activities of student in learning mathematic also low. This cause is motivation of student in learn mathematic is low.Another that student feel scare ask to their teacher about the subject they dont understand. The purpose of the research is to know that using learning strategy Teams Games Tournament (TGT) can increase activities and evaluation of learn mathematic students. The kind of research about action of class in one siclus. This siclus consist of four meeting (including one meeting for test).THe subject of research is students class XI IPA MAS TI Batang Kabung Padang TP 2013/2014 that total of students are 21 students, consist of 13 man and 8 woman. Analysis data of research is student activity and data of evaluation study of student with using comparison presentase activity students, avarage of class and presentase completeness  klasikal learning in learning using strategy TGT. The result data of analysis in this siclus get avarage of class 85,7.presentase completeness of clasiccal 81,6 % (18 students completeness). Based on the avarage  of students presentase of completeness  clasikal and avarage activity are increase.That can conclude  that strategy TGT can increase activity and evaluation of learning mathematic students.